Funky Distance Function

Calculus Level 3

Let d ( x , [ a , b ] ) = m i n x y : a y b ) d(x, [a, b])=min{|x-y|:a\leq y\leq b}) . A function f ( x ) f(x) is defined by f ( x ) = d ( x , [ 0 , 1 ] ) d ( x , [ 0 , 1 ] ) + d ( x , [ 2 , 3 ] ) f(x)=\frac{d(x, [0, 1])}{d(x, [0, 1])+d(x, [2, 3])}

Which of the following statements are true:

A: f ( f ( x ) ) = 0 f(f(x))=0

B: The graph of f ( x ) f(x) is symmetrical with respect to one of the points on the graph.

C: If the combined length of intervals on which f ( x ) = 0 f(x)=0 is a a , then the combined length of intervals on which f ( x ) = 0 f'(x)=0 is 2 a 2a and the combined length of intervals on which f ( x ) = 0 f''(x)=0 is 3 a 3a .

A A, B C None are correct B A, B, C B, C A, C

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Marta Reece
Feb 27, 2018

The function goes smoothly from limit in minus infinity of 1 2 \frac12 to a zero at x = 0 x=0 . It remain zero until x = 1 x=1 . It rises with slope 1 to the value of 1 at x = 2 x=2 . It remains at 1 until x = 3 x=3 . From the point ( 3 , 1 ) (3, 1) , it drops smoothly to its limit of 1 2 \frac12 at infinity.

...

Statement A:

The range of the function is [ 0 , 1 ] [0, 1] and f ( x ) = 0 f(x)=0 on [ 0 , 1 ] [0, 1] , so statement A is true.

...

Statement B:

The function is symmetrical around the point ( 1.5 , 0.5 ) (1.5, 0.5) . This is easy to see for values from 0 0 to 3 3 .

Above x = 3 x=3 the function f ( x ) = x 1 x 1 + x 3 = x 1 2 x 4 f(x)=\frac{x-1}{x-1+x-3}=\frac{x-1}{2x-4} .

Below zero f ( x ) = x x x + 2 = x 2 x + 2 f(x)=\frac {-x}{-x-x+2}=\frac {-x}{-2x+2} . This can be flipped around y y -axis to make x 2 x + 2 \frac x{2x+2} , then around x x -axis to get x 2 x + 2 \frac {-x}{2x+2} , add 1 to that x 2 x + 2 + 1 = x 2 x + 2 + 2 x + 2 2 x + 2 = x + 2 2 x + 2 \frac {-x}{2x+2}+1=\frac {-x}{2x+2}+\frac {2x+2}{2x+2}=\frac {x+2}{2x+2} , and finally slide that 3 units to the right (to the location of the part of the function we are trying to compare this to) x 3 + 2 2 ( x 3 ) + 2 = x 1 2 x 4 \frac {x-3+2}{2(x-3)+2}=\frac {x-1}{2x-4} . This is indeed the value of f ( x ) f(x) in that region, so the symmetry holds.

...

Statement C:

The function is equal zero on the interval [ 0 , 1 ] [0, 1] . The first derivative is zero on ( 0 , 1 ) (0, 1) and ( 2 , 3 ) (2, 3) . The second derivative is zero on ( 0 , 1 ) , ( 1 , 2 ) (0, 1), (1, 2) , and ( 2 , 3 ) (2, 3) . So the statement is true with a = 1 a=1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...